Cold Snare Polypectomy for Large Sessile Colonic Polyps: A Single-Center Experience - Thiruvengadam Muniraj; Ara Sahakian; Maria M. Ciarleglio; Yanhong Deng; Harry R. Aslanian (Gastroenterology Research and Practice, 2015)
Colonoscopic polypectomy has been shown to reduce the risk of colorectal cancer and the mortality. Postpolypectomy bleeding was reported to be lower with cold snare polypectomy (CSP) when compared with conventional polypectomy. CSP has traditionally been utilized only in smaller polyps below 1 cm. We retrospectively analyzed the CSP outcomes in patients with sessile polyps ≥10 mm in size and observed that CSP was feasible in large sessile polyps with no adverse events and with an acceptable rate of residual polyp on follow-up colonoscopy. Further prospective study in larger patient groups is warranted to determine optimal CSP techniques and whether CSP for large polyps has favorable efficacy in regard to complete polypectomy, procedure time, and complication rates relative to polypectomy with cautery.